Influência social na comunidade virtual, engajamento com a marca e a propensão do consumidor a colaborar no NPD - Grillo, Tito Luciano Hermes (2014)
Cocreation with consumers in new product development (NPD) processes has been consistently discussed in the field of marketing. Nevertheless, several aspects about this topic still are notably inceptive for scholars and managers. Among these aspects, researchers stress the understanding on how customer motivation to cocreate with organizations is established, since organizations often face challenges to have their customers willing to effectively participate in service or product development activities. Propositions to explain customer motivation to cocreate with the organization have outpointed brand virtual community phenomena, drawing associations with social stimuli, and the customer engagement concept, arguing that social factors are capable to stimulate the costumer to narrow his bond and actions with the brand and that engagement may function as a route to value cocreation. In this dissertation, a model that relates social influence in brand community, engagement with a brand and customer willingness to collaborate in NPD is proposed. In order to test the model, first, a study was conducted specifically for the proposition and the test of a measure for the assessment of the customer willingness construct. Using this measure, along with extant scales, a second study was conducted in order to test the model with members of a brand virtual community. In both studies, multivariate data analysis techniques for structural equation modeling were employed. Also, both studies were conducted in the context of the electronic games industry. The measure for customer willingness to collaborate in NPD was shown to be reliable and valid in both the analyses. Social influence processes in the virtual community did not present significant predictive effects on customer engagement, but engagement was shown to be a relevant predictor of customer willingness to collaborate in NPD. Thus, this research accounts for relevant findings for the topics of engagement and customer interaction in new product projects and stimulates discussion for future research.